The effect of multiple nutritional factors on hypothyroidism - a systemic review - Chaberska, Iwona; Feruś, Aleksandra; Lipska, Julia; Turek, Monika; Wojciechowska, Klara; Piątkowska, Karolina; Jaroń, Aleksandra; Jastrzębska, Katarzyna (Quality in Sport, 2024)
Objective: The study aims to investigate the impact of various supplements, namely selenium, vitamin D, zinc, magnesium, vitamin A, iodine, L-carnitine, and proteolytic enzymes, on the management of hypothyroidism, with a particular focus on Hashimoto’s thyroiditis. Materials and Methods: The PubMed database was searched using the keywords „Hashimoto,” „hypothyroidism,” „sport,” „physical activity,” and „diet.” Results: Several studies show that supplements can help manage hypothyroidism. Vitamin D lowers TSH levels, with varying effects on thyroid hormones. Selenium reduces TPOAb, TGAb, and TSH levels, and boosts antioxidant activity, indicating potential immune benefits. Zinc is crucial for thyroid hormone synthesis, with supplementation improving fT3 levels. Magnesium and vitamin A together enhance thyroid function and reduce inflammation. Adequate iodine intake supports thyroid function, while both deficiency and excess can cause thyroid issues. L-carnitine reduces fatigue by enhancing energy metabolism, and proteolytic enzymes have anti-inflammatory effects, aiding autoimmune thyroid disease management. Conclusions: The study highlights the potential benefits of supplementing mentioned nutrients in managing hypothyroidism by improving thyroid function, reducing inflammation, and better overall health in hypothyroid patients. Further large-scale, long-term studies are required to confirm these findings and determine optimal dosages and combinations for better effectiveness.